An extended B-Rep solid modeling kernel integrating mesh and NURBS faces. Issue 5 (3rd September 2018) - Ferrari, Giacomo; Raffaeli, Roberto; Casciola, Giulio; Morigi, Serena
ABSTRACT: In several application contexts, virtual solid models require to integrate portions of polygonal meshes with synthetic models, designed by traditional parametric/analytical multipatches systems. The paper reports the research aiming at covering the theoretical and numerical aspects connected with an extended geometric solid modeling system, focusing on the B-Rep models and introducing the new paradigm of Extended B-Rep (EB-Rep), which is able to integrate mesh-faces as part of a B-rep model. This paradigm introduces a notion of continuity between parametric and discrete representations, regularized Boolean Operations, a join operator and an approach to represent a valence semi-regular mesh as an EB-Rep structure. A prototype of the geometric solid modeling kernel has been realized and tested in the OpenCascade library environment. GRAPHICAL ABSTRACT: